2019
DOI: 10.1002/jssc.201801021
|View full text |Cite
|
Sign up to set email alerts
|

Identification of flavonoids in Dendrobium huoshanense and comparison with those in allied species of Dendrobium by TLC, HPLC and HPLC coupled with electrospray ionization multi‐stage tandem MS analyses

Abstract: Dendrobium huoshanense, a unique species in the genus Orchidaceae, is only found in China and is known as “mihu”. Due to the lack of quality control, the use of D. huoshanense in the herbal market has been limited. In this study, methods based on thin‐layer chromatography, high‐performance liquid chromatography and high‐performance liquid chromatography coupled with electrospray ionization multi‐stage tandem mass spectrometry were used to identify the flavonoids in D. huoshanense and distinguish this species f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 31 publications
2
27
0
1
Order By: Relevance
“…Similarly, our results showed that the content of total flavonoids is concentrated in the leaves, but it is higher in the roots of D. huoshanense, suggesting that roots might also be a new source for D. huoshanense. Previous study has described identification and separation of chemical constituents of flavonoids (including new glycosyl flavonoids) in D. huoshanense by various methods 6,33 . However, limited studies have focused on the flavonoids biosynthesis in Dendrobium species.…”
Section: Identification Of Degs In Polysaccharide and Flavonoid Biosymentioning
confidence: 99%
“…Similarly, our results showed that the content of total flavonoids is concentrated in the leaves, but it is higher in the roots of D. huoshanense, suggesting that roots might also be a new source for D. huoshanense. Previous study has described identification and separation of chemical constituents of flavonoids (including new glycosyl flavonoids) in D. huoshanense by various methods 6,33 . However, limited studies have focused on the flavonoids biosynthesis in Dendrobium species.…”
Section: Identification Of Degs In Polysaccharide and Flavonoid Biosymentioning
confidence: 99%
“…Apart from D. officinale , the genus Dendrobium contains over 40 species with high medicinal values [28]. The detailed metabolic profiles in the leaves and stems of D. officinale generated in the present study will facilitate cross-species comparison of key bioactive components [20,29,30]. Moreover, since most of the identified metabolites in this study have not yet been reported in Dendrobium officinale metabolic network, our work offers prospects for new bioactive compound discovery.…”
Section: Resultsmentioning
confidence: 94%
“…It is necessary to point out that, by comparing the existing literature, not only common components but also unique components exist in the plants of the Dendrobium genus, which greatly contributes to the quality control research of Dendrobium. For example, in our recent study, we systematically identified more than 20 flavonoids in D. huoshanense and found that two unique flavonoids could serve as chemical makers to distinguish it from other Dendrobium species [23]. According to the commonality and specificity of flavonoid glycosides components in D. officinale , the differences in intensity of rutin, violanthin, and isoviolanthin can be used to divided D. officinale into four categories: Danxia landform species, Yunnan Guangnan species, Guangxi Tiepilan species, and native species from Zhejiang [22].…”
Section: Introductionmentioning
confidence: 99%
“…(D. fimbriatum) [20,21]. In our previous studies, HPLC characteristic chromatogram of D. officinale, D. denneaum, and D. huoshanense have been established, successively in particular, D. officinale from different areas could be classified into four categories by HPLC characteristic chromatogram and chemometric methods [14,[22][23][24]. In addition, we also identified many flavonoids, most of which were flavonoid C-glycosides, in D. officinale, D. denneaum, and D. huoshanense.…”
mentioning
confidence: 99%